Textbook Evaluation According to Outcome-Based Education (OBE) Principles - Damayanti, Leoni; Emaliana, Ive; Kusumawardani, Irene Nany (OKARA: Jurnal Bahasa dan Sastra, 2021)
Outcome-Based Education (OBE) is known as the new curriculum that seeks students' outcomes after learning about the materials. According to that, an evaluation through the textbook, as the most-used source in teaching English, especially in Extensive Reading, is needed. The purpose of this paper is to identify whether the textbook is suitable or not based on the OBE principles. Moreover, some capable lecturers participated in evaluating this textbook using a reliable checklist. This research used a descriptive quantitative method with the results showed that in terms of module contents, this textbook is 'very poor,' in terms of module language items, this textbook is 'poor,' then in terms of module presentation expediency, this textbook is 'very poor.' The findings of this study pointed out many lacks of the textbook that need improvement.